1-Nitro-2-phenylethane: a promising phytoconstituent to modulate neuroinflammation and oxidative stress with repercussions on neurological and psychiatric disorders - Pantoja, Lucas Villar Pedrosa Silva; Fonseca, Emily Christie Maia; Souza-Junior, Fábio José Coelho; da Conceição, Brenda Costa; Farias, Sarah Viana; da Silva, Joyce Kelly R.; Maia, José Guilherme Soares; Silva, Pedro Iuri Castro; Freitas, Jofre Jacob Silva; Prediger, Rui Daniel; Campos, Daniele Luz; Fontes-Júnior, Enéas Andrade; et al. (Frontiers in Pharmacology, 2025)
Neurologic and neuropsychiatric disorders are complex, with common pathophysiological mechanisms associated with inflammation, oxidative stress, and vascular damage. These shared features have stimulated interest in bioactive compounds with neuropharmacological potential. In this regard, the 1-Nitro-2-Phenylethane (1N2PE) emerges as a promissory compound to act on the multiple via of brain disturbances. However, its neuropharmacological mechanisms of action remain largely unknown. We aim to provide a comprehensive overview of the scarce literature on the effects of 1N2PE in brain disorders to highlight the importance of further research into the mechanisms of action and its potential applications in the field of neurology and psychiatry, focusing on the anti-inflammatory and antioxidant properties. The 1N2PE exhibits neuroprotective properties, including anti-inflammatory, antioxidant, and cholinergic-enhancing effects, which together may underlie its potential therapeutic benefits for various neuropsychiatric and neurological disorders, such as depression, anxiety, seizures, and cognitive impairments. This review compiles literature on 1N2PE potential central nervous system activities, highlighting its therapeutic potential in treating behavioral and neurological disorders. Despite promising findings, further research is essential to fully understand 1N2PE as a novel therapeutic agent.